Enhancing Athletic Recovery: Scar Treatment Using Microneedling, Dermal Fillers, and Lasers - Krzysztof Kuźma; Eliza Jakubowska; Ewa Hoppe-Mitera; Irena Sionek; Anita Pakuła; Julia Ślemp; Karolina Bierć; Marcelina Grochowska; Ewelina Kisiel-Cybula (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Scars represent a prevalent skin irregularity encountered by a significant portion of the population. Beyond merely impacting physical appearance, they can also contribute to the onset of depression and anxiety disorders, which may hinder athletic recovery. The treatment landscape for scars is diverse, spanning non-invasive to invasive procedures. This literature review endeavors to explore scar management, particularly focusing on methodologies involving microneedling, dermal fillers, and laser interventions. By examining these innovative approaches, we aim to provide insights into their efficacy and implications for clinical practice, with a particular emphasis on facilitating a faster return to sport and optimal athletic performance. Material and methods: The literature was conducted using "Pub Med" and "Google Scholar" databases with the keywords "scars", "microneedling", "dermal fillers", "lasers" Brief description of the state of knowledge: Scar therapy using microneedling, dermal fillers, and lasers has shown high effectiveness and significantly improves the lives of patients undergoing treatment. Results and conclusions: Treating scars using microneedling, dermal fillers, and laser therapy has led to significant enhancements in both physical functioning and psychological well-being among patients with visible scars. These procedures exert their efficacy by promoting collagen synthesis and facilitating skin regeneration, thereby ameliorating skin redness, erythema, and scar tissue formation. However, it's important to note that the effectiveness of these interventions varies depending on factors such as the type and depth of the scar, as well as the age of the patient.